Stephen C. Soong y John Minford (eds.), Trees on the Mountain; An Anthology of New Chinese Writing, Hong Kong, The Chinese University of Hong Kong, 1984. Pp. vi + 396 - Maeth Ch., Russell (Estudios de Asia y África, 1986)
-